2021
DOI: 10.1371/journal.pone.0244614
|View full text |Cite
|
Sign up to set email alerts
|

Micro-incision vitrectomy surgery for primary rhegmatogenous retinal detachments with posterior vitreous detachments in elderly patients: Preoperative characteristics and surgical outcomes

Abstract: Purpose To assess the preoperative characteristics and surgical outcomes of using micro-incision vitrectomy surgery (MIVS) to treat RRD with posterior vitreous detachment (PVD) in an older and a younger patient group. Methods This retrospective cohort study included 407 eyes from 397 patients with primary RRD with PVD who were consecutively treated in our hospital from February 2016 to February 2020. PVD was diagnosed clinically by the presence of a Weiss ring, or was diagnosed morphologically via optical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Most PDR patients hospitalized for surgery were in the working population, whereas IHM patients in the control group tended to be older when they underwent surgery. It is wellknown that the vitreous becomes more liquefied with age (35). During surgery, we found that vitreous liquefaction occurred in most participants, resulting in a more uniform distribution of factors tested in the vitreous fluid.…”
Section: Discussionmentioning
confidence: 56%
“…Most PDR patients hospitalized for surgery were in the working population, whereas IHM patients in the control group tended to be older when they underwent surgery. It is wellknown that the vitreous becomes more liquefied with age (35). During surgery, we found that vitreous liquefaction occurred in most participants, resulting in a more uniform distribution of factors tested in the vitreous fluid.…”
Section: Discussionmentioning
confidence: 56%
“…Only 6% of patients in this study were aged 80 or older. A report from Japan found no difference in the anatomical outcomes of vitrectomy for retinal detachment in elderly and young patients, however, their definition of elderly was >70 years [ 16 ]. In Israel, a study of vitrectomy outcomes in patients aged 85 or older found primary anatomical failure occurred in 45% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Prince Charles Eye Unit King Edward VII Hospital, Windsor, UK. 16 Royal Victoria Infirmary, Newcastle upon Tyne, UK. 17 East Suffolk & North Essex NHS Foundation Trust, Essex, UK.…”
mentioning
confidence: 99%
“…8 9 Some studies have indicated that older age is associated with worse outcomes, 10 while others have shown younger patients have worse outcomes or that there is no difference between the two populations. [11][12][13] There have been few studies comparing outcomes of SB, PPV and PR in young patients given the relative rarity of primary RRDs in younger patients. Election of treatment options for young patients tend to ultimately revolve around surgeons' preference or facilities'availability.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Given that ageing and PVD are major risk factors for retinal detachment, sample sizes for young (<50 years of age) patients are under-represented in these studies and the effect of age on RRD outcomes remains less clear 8 9. Some studies have indicated that older age is associated with worse outcomes,10 while others have shown younger patients have worse outcomes or that there is no difference between the two populations 11–13…”
Section: Introductionmentioning
confidence: 99%